Numerical Analysis for Nano-Powell-Erying Fluid Flow Past a Stretching Porous Surface with Effects of Magnetic Field, Thermal and Mass Biot Numbers - B. Chandrasekhar (Mathematical Statistician and Engineering Applications, 2022)
This work investigates Powell-Eyring nanofluid flow in two dimensions across a stretched sheet. The authors analysed a flow that was viscous, constant, incompressible, electrically conducting, and uniform. Consideration of Powell-Erying nanofluids leads to a set of equations in the presence of thermodynamic and mass Biot numbers, thermophoresis, and Brownian motion phenomena. Similarly, when Brownian motion phenomena are at play, these conditions hold true. By relating the applicable alterations, the fundamental calculations that regulate flow may remain concentrated to a set of ordinary disparity calculations. The simplified scheme of equations is now explained using either the Runge-Kutta technique laterally the Shooting method. Several engineering components and their effects on the variables of rapidity, temperature & attentiveness are graphically depicted. The Sherwood figure, Nusselt number, also skin-friction coefficient remain all included in the tables below. By comparing our findings to those published in the scholarly publications in question, we are able to verify the reliability of the code and the accuracy of the numerical scheme.